2013
DOI: 10.1073/pnas.1222047110
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Thy1+NK cells to protective IFN-γ production duringSalmonellaTyphimurium infections

Abstract: IFN-γ is critical for immunity against infections with intracellular pathogens, such as Salmonella enterica . However, which of the many cell types capable of producing IFN-γ controls Salmonella infections remains unclear. Using a mouse model of systemic Salmonella infection, we observed that only a lack of all lymphocytes or CD90 (Thy1) + cells, but not the absence of T cells, Retinoic acid-related orphan receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 53 publications
10
86
0
Order By: Relevance
“…Consistent with this idea, splenic NK cells are a prominent cellular source of innate IFN-␥ production in models of systemic S. Typhimurium infection (12)(13)(14). Furthermore, CD1D-restricted NKT cells contribute to innate IFN-␥ production in the livers and spleens of mice with disseminated S. Typhimurium infection (15,16).…”
mentioning
confidence: 78%
“…Consistent with this idea, splenic NK cells are a prominent cellular source of innate IFN-␥ production in models of systemic S. Typhimurium infection (12)(13)(14). Furthermore, CD1D-restricted NKT cells contribute to innate IFN-␥ production in the livers and spleens of mice with disseminated S. Typhimurium infection (15,16).…”
mentioning
confidence: 78%
“…Previous studies have suggested differing roles of neutrophils, macrophages, T lymphocytes, and NK and NKT cells in contributing to IFN-g production during primary Salmonella infection (47-49, 73, 74). Recently, Kupz et al (75) showed that Thy1-expressing precursor and immature NK cells are critical in antibacterial immunity via IFN-g-dependent control of S. Typhimurium. In addition, NK and NKT cells are reported to be early producers of IFN-g from healthy human adult blood lymphocytes stimulated ex vivo with NTS contributing to protection from bacteremia (76).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analysis confirmed that T cells are not required for the initiation of the "plateau phase" (43,44) and that NK T cells (35) and B cells (33,34) are not essential for clearance of a primary infection. Important new findings from this comprehensive study include data showing (i) that the IFN-␥ that is required for early control of Salmonella may come from a variety of cell types and that NK cells and memory CD8 ϩ T cells alone are sufficient to produce enough IFN-␥ to enable control of the initial exponential growth of the bacteria (13,14); (ii) that in the absence of CD4 ϩ T cells, CD8 ϩ and DN T cells contribute to the control of S. Typhimurium and prevent mice from becoming moribund due to high bacterial numbers (deficiency of classical, nonclassical, or all CD8 ϩ T cell alone has no impact on the outcome of the infection); and (iii) that IFN-␥ levels at later stages of the infection appear to be a correlate of bacterial burden rather than a mediator of clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have demonstrated crucial roles for both CD4 ϩ T cells and IFN-␥ in antiSalmonella immunity (7,12,13), until recently it was not clear whether these deficiencies are causally linked. We have recently shown that the production of IFN-␥ by NK cells or memory CD8 ϩ T cells in the absence of all other IFN-␥-producing lymphocytes is an important contributor to early host-protection (13)(14)(15). These results indicated an inherent capacity of non-CD4 immune cells to contribute to anti-Salmonella immunity.…”
mentioning
confidence: 98%
See 1 more Smart Citation